Petrophysical characteristics and identification parameters of the Jurassic continental shale oil reservoirs in the Central Sichuan Basin. (18th January 2023) - Song, Yichen; Zeng, Lianbo; Gong, Fei; Huang, Ping; Lyu, Wenya; Dong, Shaoqun
Abstract: The Sichuan Basin in south-western China is rich in shale oil in the Jurassic strata. Due to its complex geological characteristics, reservoir identification using current log-constrained seismic inversion methods is difficult. Characteristics of the shale oil reservoirs were tested on the basis of the petrophysical experimentation of core samples from the said strata. Thin sections and logging data analysis showed the influencing factors on petrophysical characteristics and clarified the sensitive geophysical parameters for reservoir identification. The Da'anzhai Member reservoirs were determined to have high acoustic velocities, V p / V s ratios and Young's moduli, and low Poisson's ratios. Several geological factors have influenced the petrophysical properties of the reservoirs. The Da'anzhai Member reservoirs are characterized by a low content of clay minerals and the development of fractures and laminae. The presence of clay minerals caused general high acoustic velocities of the reservoirs; the presence of fractures and laminae in high-quality reservoirs results in a decrease of the acoustic velocities. Therefore, the relatively low value against the background of high acoustic velocity can be used as the criteria for high-quality reservoirs. Poisson's ratio is obviously different in reservoirs and non-reservoirs. When it is <0.269, the reservoirs can be fully identified. In addition, the combination of the Lame constant and shear modulus (λ > 25.277 and μ > 20.72 GPa), P-wave and S-wave velocity ( V p  > 4967 and V s  > 2781 m s −1 ), wave impedance and V p / V s ratio (AI > 13.319 g · cm 3  · km · s −1 and V p / V s  > 1.792) can also provide references for reservoir identification.